On large deviations for random sums of the squares of weighted Gaussian random variables - Kasparavičiūtė, Aurelija; Deltuvienė, Dovilė (Lietuvos matematikos rinkinys, 2015)
The paper considers normal approximation to the distribution of random sums of the squares of independent weighted Gaussian random variables (r.vs.) taking into consideration large deviations in the Cramér zone.
Keywords: cumulant method; large deviations; Gaussian sequence